Towards a comprehensive understanding of science practices: a heuristic for increasing educator familiarity across a series of science education frameworks - Ashli M. Wright; Marie Janelle Tacloban; Shelby Lake; Melissa McCartney (Springer, 2024)
Abstract Scientific practices describe behaviors scientists engage in while investigating the natural world. Educators should be aware of different science practice frameworks to better understand their students' progression for learning science practices across the K-20 spectrum. For example, a high school AP instructor would benefit from understanding both the K-12 frameworks their students have already experienced and the future undergraduate frameworks their students are moving toward. We were interested in exploring educator familiarity with the scientific practices outlined in the Next Generation Science and Engineering Practices, the Advanced Placement Science Practices, and Vision & Change Core Competencies. In practice, all science educators are teaching the same set of core principles around which these different frameworks are built. Under this view, it is a missed opportunity to not consider or draw on different frameworks to expand one's teaching practice. Using a cognitive constructionist approach, we describe the implementation of the "Science Practice Frameworks Concept Map Activity," designed to (1) introduce educators to scientific practices contained within Science Practice Frameworks and (2) show educators that despite these science practices targeting different student populations they are, at their core, very similar and often overlap. We present data showing a positive shift in educator familiarity with Science Practice Frameworks and present examples of participant concept maps that help us begin to understand how educators perceive the frameworks and the relationships between them, ensuring that educators are better prepared to guide students through a comprehensive understanding of science practices.